The retroverted dens: a review of its anatomy, terminology, and clinical significance - Ishak, Basem; Dhaliwal, Gunveer; Rengifo, Roxanne; McCormack, Erin; Mathkour, Mansour; Iwanaga, Joe; Bui, C. J.; Dumont, Aaron S.; Tubbs, R. Shane (World neurosurgery, 2020)
Background - Little attention has been given to the retroverted dens within the existing medical literature. However, this finding can have a clinical impact, especially in patients with Chiari malformation type I (CM1), as it can have consequences for further treatment. - Methods - Using standard search engines, we performed a literature review of anatomical, radiologic, and clinical studies as well as pathologic and surgical considerations related to the retroverted dens. Key words for our search included retroverted dens; retroflexed dens; odontoid retroflexion; posterior inclination; and tilted dens. - Results - A retroverted dens is most commonly found in the pediatric population in relation to CM1. Research has demonstrated that high degree of dens angulation can result in significant anterior brain stem compression with the need for both anterior and posterior decompression in patients with symptomatic CM1. - Conclusions - A greater degree of dens angulation can lead to neurologic symptoms secondary to spinomedullary compression. Therefore, correct measurements are essential as such findings can influence presurgical planning.